The Learning Curve for Thermal Ablation of Liver Cancers: 4,363-Session Experience for a Single Central in 18 Years - Jing, Xiang; Zhou, Yan; Ding, Jianmin; Wang, Yijun; Qin, Zhengyi; Wang, Yandong; Zhou, Hongyu (Frontiers in Oncology, 2020)
This study aimed to explore the special efforts required to achieve proficiency in performing thermal ablation of liver cancers, including tumors in difficult locations, and clarify the effects of handing-down teaching on the corresponding process. Major complications of patients receiving percutaneous thermal ablation of liver cancer were analyzed. Polynomial fitting was used to describe the connection between major complication rates and special experience. Learning curve of major complications was plotted both for the whole group and for each operator, respectively. Tumors in difficult locations were further studied. A total of 4363 thermal ablation sessions were included in this study. 143 of 4363 patients had major complications, corresponding to an incidence rate of 3.27%. 806 thermal ablation sessions were performed for tumors in difficult locations. The major complication rate of these sessions is 6.33%. According to the trend of the learning curve of the 4364 patients, the experience of the whole group can be classified into 5 stages, that is, the high-risk, relatively stable, unstable, proficient and stable periods. A learning curve for an individual operator can be classified into the high-risk, proficient and stable period. The major complication rates for the chronologically first, second and third operator of the group are 3.23%, 3.35% and 3.31%, respectively. The special experience needed to bypass the first stage corresponds to 410, 510 and 440 sessions, the second stage, 1850, 850 and 870 sessions, for the three operators, respectively. The major complication rates for the tumors in difficult locations for the first, second and third operator were 7.04%, 5.53% and 5.98%, respectively. For these tumors, the special experience needed to bypass the first stage corresponds to 150, 130 and 140 sessions, the second stage, 290, 175 and 185 sessions, for the three operators, respectively. In conclusion, the learning process of an operator percutaneous thermal ablation for liver cancer can be classified into three stages. The major complication rates for tumors in difficult locations were higher than that for all tumors. Handing-down teaching can make an operator arrive at the third stage earlier but not the second stage.